Revisión y actualización de las técnicas diagnósticas en las condidiasis - Freijóo, Y. Capintero; Cerdeira, M.C Rodríguez (Brazilian Journal of Sexually Transmitted Diseases, 1997)
Considering about the great increase of fungai infections above ali in immunocompromised patients, a review of the diagnostic techniques used now in the laboratories of clinicai microbiology and methods which in the future, will enable a rapid and especific diagnosis.